Case Report: Biallelic Variant in the tRNA Methyltransferase Domain of the AlkB Homolog 8 Causes Syndromic Intellectual Disability - Waqas, Ahmed; Nayab, Anam; Shaheen, Shabnam; Abbas, Safdar; Latif, Muhammad; Rafeeq, Misbahuddin M.; Al-Dhuayan, Ibtesam S.; Alqosaibi, Amany I.; Alnamshan, Mashael M.; Sain, Ziaullah M.; Habib, Alaa Hamed; Alam, Qamre; et al. (Frontiers in Genetics, 2022)
Intellectual disability (ID) has become very common and an extremely heterogeneous disorder, where the patients face many challenges with deficits in the intellectual functioning and adaptive behaviors. A single family having three affected individuals revealed severe disease phenotype such as intellectual disability, developmental delay, dysmorphic facial features, postaxial polydactyly type B and speech impairment. DNA of a single affected individual was directly subjected to whole exome sequencing, followed by Sanger sequencing in all the available members of the family, and revealed a biallelic nonsense mutation (c.1511G>C; p.Trp504Ser) in the ALKBH8 gene, which plays a very important role in the tRNA modifications. Our finding adds another variant to the growing list of ALKBH8 associated tRNA modifications causing intellectual disability and additional phenotypic manifestations. The present study clearly depicts the key role of genes associated with tRNA modifications such as ALKBH8 in the development and pathophysiology of human brain.